Carreadores lipídicos nanoestruturados como estratégia para incorporação do filtro solar Bemotrizinol - Medeiros, Thayse Silva (2019)
Skin cancer is currently the most common type in the world, accounting for 33% of cancer cases in Brazil. Thus, in order to prevent skin cancer, premature aging and other inconveniences related to exposure to UV radiation, there is growing interest and research on photoprotectors. However, the risk of photodegradation, skin permeation and systemic absorption of these products diminishes their safety. In addition, the high lipophilicity of conventional sunscreens and low skin permanence lead to improper use, reducing effectiveness. An alternative to overcoming such deadlocks is the incorporation of sunscreens into nanostructured lipid carriers (NLC), which are aqueous dispersions of nanoparticles formed by mixtures of solid and liquid lipids. In this study, NLC containing the organic UV filter bemotrizinol (BEMT), which has a broad absorption spectrum and increased photostability, was developed and characterized using carnauba wax (solid lipid) and caprylic and caprylic acid triglyceride (liquid lipid) by ultrasound technique. A Box-Behnken experimental design was performed to optimize the NLC and evaluate the influence of three independent variables on particle size, so the ideal system was chosen for characterization. The particle size was evaluated using the dynamic light scattering (DLS) technique and decreased as the surfactant concentration increased, being analyzed up to 30 days of storage, presenting at 122.4 ± 0.3 nm on the last day. Scanning electron microscopy showed spherical particles, intact and without clusters. Analyzes of thermogravimetry, differential exploratory calorimetry, and Fourier transform infrared spectroscopy confirm the incorporation of sunscreen in nanocarriers. X-ray diffraction allows observing the reduction of crystallinity in the NLC, desired result for the nanosystem. Qualitative and quantitative in vitro analyzes performed by ultraviolet spectroscopy indicated that an increase in sunscreen photoprotective activity was observed when incorporated into the NLC. Thus, the results suggest that the developed NLC can be an innovative, promising, stable and biocompatible system for use in sunscreens.